Metamorfismo das rochas de alto grau do complexo Tartarugal Grande, região de Ferreira Gomes – Amapá - RODRIGUES, Paulo Ronny Soares (2020)
The region of Tartarugal Grande Complex (TGC), situated at the western-central portion of the Amapá state, corresponds to a crustal segment constituted by an assembly of high grade metamorphic rocks, among felsic and mafic granulites and leucogneisses. Felsic granulites may be classified as charnockitic, enderbitic and charnoenderbitic granulites, in addition to miclocline charnockites, whislt the leucogneisses may be garnet or cordierite-rich. The high grade metamorphic rocks from TGC present, mainly, granoblastic texture, with preservation, in some cases, of reliquiar igneous texture. Micropertitic microclines are common and, sometimes, even mesopertites. Deformational microstructures from TGC include ductile and ruptile deformation, as undulose extinction, deformed twinning, exsolution and microfractures features. Deformational processes acting with the metamorphism progress involve dynamic recrystallization, with grain boundary migration and subgrains formation. The influence of regional shear zones is recorded mainly in leucogneisses and is responsible for the mylonitic texture and subgrains throughout the porfiroclastos of microcline. The conditions of the metamorphic peak for these rocks achieved 800 to 850 °C and 6 to 8 Kbars and are compatible with the stability field of the association cordierite + garnet + quartz + microcline, present in leucogneisses, and quartz + ortopyroxene + garnet, present in felsic granulites. Mafic granulites have a paragenesis composed by ortopyroxene + clinopyroxene + plagioclase + hornblende, and the absence of olivine suggests conditions of metamorphic peak <850°C. Felsic granulites present evidences of local anatexis, with small scale and irregular neossomes. Retrometamorphism is common in the majority of the rocks from TGC and it is evidenced by reactions of garnet break, to formation of biotite and quartz, and pyroxene, to the formation of hornblende.